Retention Effect of Dual Task Training on Mobility, Fear of Fall and Quality of Life in Subjects with Parkinson's Disease. - Chandraprabha, A.; SudheeraKunduru (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Impairment in the ability to perform another task while walking i.e., dual tasking is associated with an increased risk of fall, diminished mobility, loss of independence leading to decrease in the quality of life among patients with Parkinson's disease. So, the present study aims to determine the retention effect of dual task training on mobility, fear of fall, quality of life. Method: 30 subjects between the age group of 65-75 years diagnosed with PD were included in the study and were allocated to a single group after fulfilling inclusion and exclusion criteria. Baseline data like age, gender, Hoehn&Yahr stage was noted. Subjects underwent dual task training 5 times a week, for 4 weeks. All the subjects were assessed using Timed Up and Go test, Fall Efficacy Scale and Parkinson's Disease Questionnaire-39. Results: The dual task training on mobility showed significant improvement in mobility, fear of fall and quality of life in post-test 1. Retention effect (post-test 2) also showed significant improvement but compared to post-test 1 (p<0.001), it has reduced (p<0.05). Conclusion: The result of present study shows significant retention effect of dual task training on mobility, fear of fall and quality of life. The results also show that regular training is required for the subjects to maintain the progress achieved.